Chronograms and Chronostichs of the 1695 Kražiai Manuscript - Antanavičius, Darius (Senoji Lietuvos literatūra, 2015)
Eight students of the Society of Jesus, who studied rhetoric at Kražiai College in 1694–1695, left a priceless fruit of their work – a 700-page manuscript book with an intricate baroque title, Fructus horni meditationis rhetoricae Crosis ab academicis Societatis fusi et in cornucopiam depositi, sive specimina profectus in utraque eloquentia rhetorum Crosensium Societatis Iesu anno M DC XCV sub reverendo patre Petro Puzyna professore dignissimo (Annual fruits of rhetorical meditation gathered and laid in a cornucopia in Kražiai by students of the Society of Jesus, or work samples in either rhetoric by students of the class of rhetoric at Kražiai College under the tutorship of Reverend Father Peter Puzyna, the most valuable professor of the year 1695), which is kept at Czartoryski Library in Cracow (manuscript 1866 IV). This paper focuses on the chronograms and chronostichs of the 1695 Kražiai manuscript.Up until now, literature has suggested only one way of composing and counting of chronograms and chronostichs, which is the arithmetical sum of the number-denoting letters of the Latin alphabet – M, D, C, L, V, and I, completely disregarding their sequence within the text. Most of the chronograms and chronostichs of the 1695 Kražiai manuscript do not comply with this principle. The aim of the paper is to introduce the cases detected and to determine their correct dating and the method of counting.Thirty chronograms and chronostichs were found in the 1695 Kražiai manuscript. In the paper, the original variants with the indication of their nature (chronostich or chronogram) and metre, with the calculation of their dates, and with their translations into Lithuanian are presented in sequential order.The different dates of these thirty chronograms and chronostichs that result from the application of the accepted method of their counting give cause for surprise: with 1715 as the dominating date, there are five instances of 1695, one of 1694, and even one of 1905 (!).What mystery hides behind 1715? If it is correct and corresponds to the authors’ line of thought, what could it mean and how could it be justified in the manuscript of 1695? Nothing definite can be said with regard to this question. Different consideration can take one as far as to cast doubts on the time of the production of the manuscript, to refute the students’ time in Kražiai in 1694–1695, to invent unverifiable theories of chronologically later ‘insertion’ of these chronograms and chronostichs, and the like.Next, the paper gives three samples of manuscript notes of the rhetoric course from the Manuscript Department of Vilnius University library on how this form of poetry used to be explained and how its composition was taught in the colleges of the Jesuit province of Lithuania in the late seventeenth century. These samples show that students were taught the elements of chronograms and their composition. It also becomes obvious that no other method of their composition and counting was referred to except the arithmetical sum of the number-denoting letters disregarding their sequence in the text. Thus the manuscript material of the rhetoric course does not offer any food for thought on how else the chronograms of the 1695 Kražiai manuscript could be counted, which means we have to do it ourselves.A closer look shows that there is a connection between the recurring 1715 and 1695, which is the even number 20. In our opinion, it is the key that could ‘unlock’ the chronograms and chronostichs analysed. We noticed that the operation of subtraction is sufficient to always turn 1715 to 1695. This can be illustrated by the example of the first chronogram, which is interlaced in the title of the manuscript: FrVCtVs hornI MeDItatIonIs rhetorICae. In order to make it more obvious, we are presenting the numbers in decreasing order: M+D+C+C=1700. We then add the first V to 1700, which results in 1705. We also add the second V and five I’s, and the result is 10. Finally, 1705–10=1695. Quod erat demonstrandum. Subtraction can be done in various ways, for example: 1700–10 (V+V or IIIII)+5 (V or IIIII)=1695, and the like.Through the application of subtraction, the seemingly illogical and strange date of 1715 turns into 1695 without any exceptions. The paper then proceeds to the counting of all chronograms. For the sake of clarity, the first method of subtraction is given.Conclusions. The method of chronogram composition and counting applied by the authors of the 1695 Kražiai manuscript has not been seen or used anywhere else. Therefore it is not clear whether it was a ‘one-off’ licentia poetica approved by the teacher in order to facilitate composition of chronograms for the students, or a search for new creative paths. Composition of six ‘regular’ chronograms, one of which is the so-called Cabbalah chronostich, raises no doubt as to the students’ talent and knowledge of mandatory rules. Hardly had such an ‘innovation’ a chance of spreading wider, for it would have been misunderstood and even treated as erroneous. We, too, were unable to explain, for quite a long time, why the counting resulted in the incomprehensible sum of ‘1715’. In this case we were much assisted by our awareness that the authors could only have the number ‘1695’ in their minds and not any other. Without such a key, a riddle like this might remain unsolved next time.
Keywords: -